Activation of coagulation and fibrinolysis after rehabilitative exercise in patientswith coronary artery disease - Weiss, Claus; Velich, Tamás; Niebauer, Josef; Hauer, Klaus; Kälberer, Barbara; Kübler, Wolfgang; Bärtsch, Peter (The American journal of cardiology, 1998)
It has been suggested that blood coagulation be activated and fibrinolytic activity be impaired in patients with coronary artery disease (CAD). With regard to the activation of coagulation and fibrinolysis occuring during exercise in healthy individuals, we examined the hypothesis that rehabilitative exercise in patients with CAD might give rise to an exaggerated activation of coagulation. In 12 patients with angiographically documented CAD without myocardial infarction within the preceding 6 months (male, age 55 ± 9 years [SD]) and in 12 healthy controls (male, 52 ± 7 years), molecular markers of thrombin, fibrin, and plasmin formation were determined before and after a rehabilitative group exercise session lasting 1 hour. Resting levels of prothrombin fragment 1+2 were lower in patients with CAD (0.67 ± 0.2 [SE] vs 1.04 ± 0.2 nmol/L, p <0.001) and remained unchanged after exercise, whereas a significant increase was noted in controls (p <0.01). After exercise, plasma levels of thrombin-antithrombin III complexes and of fibrinopeptide A increased significantly in both groups, although there were more pronounced changes in controls. Exercise resulted in a marked generation of plasmin as indicated by plasmin-α2-antiplasmin complexes increasing 2.5-fold in patients (p <0.001) and threefold in controls (p <0.001). Repeated experiments in control subjects after administration of aspirin (day 1: 500 mg; days 2 to 5: 100 mg) documented that differences between groups could not be attributed to aspirin medication (100 mg/day) in patients with CAD. We concluded that rehabilitative exercise in patients with CAD beyond the immediate postinfarction period has no detrimental effects on thrombin, fibrin, and plasmin formation.